El abordaje interdisciplinario mejora el diagnóstico de las infecciones de transmisión sexual - Bessone, Liliana Elizabeth (2013)
The National Program for Human Retroviruses, AIDS and STDs was implemented in the Arturo U. Illia Hospital in 2009. Using the information available in the pharmacy service on patients with syndromic treatment of sexually transmitted infections (STIs), in 2011 a cross-sectional descriptive study was conducted to learn about the situation of the Program records, analyze interventions carried out from the service and contribute to the knowledge of epidemiological trends. STI training activities were implemented during the second half of 2011, and a significant increase in the number of cases was observed at the end of that year. Pregnant women with syphilis and patients hospitalized for other causes were registered in the Program. The diagnosis of trichomoniasis increased significantly, with a higher proportion of women, while syphilis cases remained unchanged. The 21-50 age group was predominant. Although most were residents of Alta Gracia, patients from the area of influence of the Hospital increased in the second half. Moreover, there was an increase in the number of treatments of sexual partners and high compliance in treatment regimens. In addition, consumption of condoms supplied by the program increased two and half times over the previous semester. The excellent disposition of the professionals involved led to improved registration and the inclusion of patients in the Program, optimizing the use of resources. This helps reduce the transmission of STIs and their potential complications, it contributes to the effectiveness of treatments and knowledge of epidemiological trends, providing guidance for the implementation of new prevention efforts.